(3GdeYde HCSeGA TjhN GdHNGQi heSdes - (3GdMGaX eMeO Hf ESeGYjd Hf Ndahf GdGROj, CHh YHO Gddg,J (B636 (3g` s
(3ChdgG (B:s
(3Qhi YHO Gddg Hf CMeO Hf MfHd Yf CHjg MaGX GdOfjG CQHYI s
(3BNQgG (B:s
(3BNQg fYje Hf MeGO s
(3fSNI cJHJ fbdkG Yf fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B36s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B256 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdJGQjNs